Merits of and Technical Tips for Supra-Mesenteric Aortic Cross Clamping - Eugenio Martelli (Vascular Specialist International, 2019)
Supra-celiac aortic cross clamping is often utilized during aortic reconstruction for aneurysmal/occlusive disease involving the pararenal aorta. However, this may be accompanied a myriad of complications related to hemodynamic disturbances, cardiopulmonary compromise and hepatic ischemia. Supra-mesenteric aortic cross clamping may be an excellent option in selected patients with suitable anatomy to minimize or avoid these complications. Herein, the merits of and technical tips for supra-mesenteric aortic cross clamping are discussed.